POTENTIAL OF THERMOGRAVIMETRIC ANALYSIS COUPLED WITH MASS SPECTROMETRY FOR THE EVALUATION OF KEROGEN IN SOURCE ROCKS - Marshall C.P.; Kannangara G.S.K.; Wilson M.A.; Guerbois J.P.; Hartung-Kagi B.; Hart G. (My University, 2002)
The molecular composition of oil and yield from a source rock depends on the temperature to which the source rock is subjected. However, the yield of oil and gas represents hydrocarbons generated over a range of temperatures. A technique that measures both volatile yields and bulk and molecular compositions during volatile evolution would determine the differential effects of temperature change, thereby giving information on the effect of thermal gradients. Attaching a mass spectrometer to a thermogravimetric analyser assists in this goal since it allows gases to be analysed during petroleum source rock evaluation by pyrolysis. Single ion monitoring allows unambiguous identification of thermal events. It reveals temperature at which water, methane and carbon dioxide evolve. This allows organic and inorganic transitions to be distinguished. Parameters that describe the yields of oil and gas can also be derived from thermogravimetric analysis (TGA) in much the same way as they can for Rock-Eval pyrolysis data and are useful when combined with solid state 13C nuclear magnetic resonance (NMR) spectroscopy and Rock-Eval data for elucidating mineral matter effects.
Keywords: KEROGEN; PYROLYSIS; THERMOGRAVIMETRIC ANALYSIS; MASS SPECTROMETRY; SOURCE ROCKS; PETROLEUM